Proposed Design of Competency Based Career Path Development for Machining Job Group in PT Dirgantara Indonesia - Inayah, Inayah; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2014)
Abstract. PT. Dirgantara Indonesia is a State Owned Enterprise (SOE) that was founded in 1976, has its headquarters in Bandung and provides products and services in its business lines. PT Dirgantara Indonesia has a vision to be a world-class aerospace company based on the mastery of high technology and cost competitiveness in the global market. In mid-2010, PT. Dirgantara Indonesia was trying to show the new expectations and potential growth to become a better company. PT Dirgantara Indonesia is planning new strategy related to human resources, it is trying to restructure and stabilize the regeneration of human resources. It needs to be done because lack of motivation and a lot of employees left the company led to stagnant labor productivity. This is being happened because the company has not developed structured career planning for its employees and implementation of human resources management practice also has not well integrated. The development of competency-based career paths is one of solution to resolve the issue. Career paths are designed based on competency model that defined from the values and objectives of the company's business and also based Job Family. The research methodology used in this study is a mixed method, using both qualitative, used for collecting data from in depth interviews and reading literatures, and quantitative that used as a measurement tools to define business solution by SPSS. Development of career paths in this research using hierarchical cluster analysis for the 45 job title on machining job group by Directorate of Production based on 6 core competencies, 10 functional competencies andÂ  2 technical competencies and career path that will be developed in this research is single career path. Based on this research resulted job competency for 45 job title and grouped into three cluster on Job Family, and each job title consist of different job class. Based on three clusters will develop one cluster as whole after several stages of clustering analysis. Career path development can be implemented as part of a career management system for PT Dirgantara Indonesiaâ€™s future, so it expected to increase productivity of employee performance and succession of career planning also can be structuredKeywords: Competency, Career Path